Worldwide prevalence of mild cognitive impairment among community dwellers aged 50 years and older: a meta-analysis and systematic review of epidemiology studies. (17th August 2022) - Bai, Wei; Chen, Pan; Cai, Hong; Zhang, Qinge; Su, Zhaohui; Cheung, Teris; Jackson, Todd; Sha, Sha; Xiang, Yu-Tao
Abstract: Background: Mild cognitive impairment (MCI) is the preclinical and transitional stage between healthy ageing and dementia that may be a potential 'target' for interventions designed to delay progression to dementia. In this systematic review and meta-analysis, we assessed the prevalence of MCI worldwide in community-dwelling adults aged 50 years and older. Methods: PubMed, Web of Science, Embase and PsycINFO database searches were conducted from their respective inception dates to 1 September 2021. Data on the overall prevalence of MCI were synthesised using random effects models. Results: A total of 66 articles covering 242, 804 participants fulfilled study criteria for inclusion. The overall prevalence of MCI was 15.56% (95%CI: 13.24–18.03%). Prevalence rates of amnestic MCI and non-amnestic MCI were 10.03% (95%CI: 7.98–12.27%) and 8.72% (95%CI: 6.78–10.89%), respectively. The prevalence of MCI increased with age and decreased with education level. Subgroup and meta-regression analyses revealed that region of study site and male gender proportion per sample were significant correlates of MCI prevalence. Conclusion: The global prevalence of MCI among community dwellers is over 15% and is affected by age, gender, education level and region of study sites. Assessment and interventions targeting MCI within at-risk population subgroups should be considered toward the prevention of dementia.